Homestead- and community-scale multiple-use water services: Unlocking new investment opportunities to achieve the millennium development goals - van Koppen, Barbara; Smits, S.; Mikhail, M. (Wiley, 2009)
Since the early 2000s, a new participatory approach to water services delivery is emerging: multiple-use water services (MUS). By overcoming sectoral boundaries within the water sector, new opportunities are opened up that better align with people's practice of using water from multiple sources for multiple uses. Two opportunities are discussed in this paper on the basis of past research by the CGIAR Challenge Program on Water and Food, among others. One new opportunity is homestead-scale MUS. Providing double or triple the quantities of the design norms in the domestic subsector in poor rural and periurban areas allows water users to take up significant productive activities besides meeting domestic needs. Cost-benefit ratios are favourable. Homestead-scale MUS is the most effective way of using water to contribute to all Millennium Development Goals. A related second new opportunity is community-scale MUS. This participatory approach to water services considers communities' holistic water-and landscapes and supports incremental improvements in infrastructure according to people's own priorities and needs, which are often in favour of homestead-scale MUS. New synergies in infrastructure intakes, storage and conveyance are tapped.